Komik sebagai Media Dakwah: Analisis Semiotika Kepemimpinan Islam dalam Komik âSi Bujangâ - Nasrullah, Rulli; Sari, Novita Intan (Jurnal Ilmu Dakwah, 2012)
Comics or cartoons are a kind of medium that can be used in dakwah. Through the comics, messages are represented by visuals which tend not to seem patronizing. One of the Islamic comic used as an example for this paper is the comic entitle "Si Bujang." By using the semiotics methods, this paper tries to strip the message what is implicit or explicit in the comic is aimed at the interpretation of propaganda messages about Islamic leadership. Overall, this paper assumes that the comic is one effective medium for the propagation of Islam through the game of visual signs.